1983
DOI: 10.3758/bf03334693
|View full text |Cite
|
Sign up to set email alerts
|

Postacquisition unexpected footshock disrupts appetitively motivated instrumental performance based on short-term retention

Abstract: Water-deprived rats were trained to run for water in an E-maze on a delayed-alternation task with a 5-min retention interval. Each day, long before encountering and again long after having encountered the delayed-alternation task, all subjects consistently experienced weak footshock in Context A and no foots hock in Context B. C,,::texts A and B were highly dissimilar to each other and to the E-maze. On delayed-alternation probe trials, subjects were exposed to Context A or Context B for the middle 30 sec of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The present results add to what is known of other sources of processing interference, such as exposure of subjects to multiple to-beremembered mazes (Roberts, 1981) or to surprising stimuli during the delay (Miller & Balaz, 1983). In contrast, Terry (1987) found that simply giving a food reward during the delay interval did not adversely affect retention.…”
Section: Discussionmentioning
confidence: 33%
“…The present results add to what is known of other sources of processing interference, such as exposure of subjects to multiple to-beremembered mazes (Roberts, 1981) or to surprising stimuli during the delay (Miller & Balaz, 1983). In contrast, Terry (1987) found that simply giving a food reward during the delay interval did not adversely affect retention.…”
Section: Discussionmentioning
confidence: 33%
“…These findings are consistent with a distributive processing or limited capacity memory theory. According to Wagner's rehearsal theory, surprising stimuli are rehearsed longer in short-term memory (Maki, 1979; Terry & Wagner, 1975) and are more likely to interfere retroactively with rehearsal of previous stimuli already occupying short-term memory (Miller & Balaz, 1983; Wagner et al, 1973). This theory readily accommodates both the enhanced retention of nonrewarded locations and the retroactive interference effects produced by nonreward.…”
Section: Discussionmentioning
confidence: 99%
“…Interference with spatial memory has also been shown. Miller and Balaz (1983) interpolated an expected or surprising event in the delay interval of a food-rewarded delayed-alternation trial. There was significantly less alternation when a surprising shock followed the target than when an expected shock followed and less alternation, although not significant, when a surprising omission of shock followed the target event than when an expected absence occurred.…”
Section: Methodsmentioning
confidence: 99%